Contested Migration Tswana Women "Running Away" from the "Land of the Desert" - Cockerton, Camilla May.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Pivot, 2019)
The migrant has been designated the central or defining figure of the 20th and 21st centuries. For much of this period, research and theory have centred on adult men as representative, ignoring women's part in international migration. Similarly, in Botswana, most history books on migration focus solely on men's experiences. Weaving together history, theory and migrant women's own words, this book reveals Tswana women's multifaceted participation in the cross-border flows from colonial Botswana to pre-apartheid South Africa. Women succeeded in "running away" despite the opposition of Tswana and colonial male authorities. This book celebrates women's agency and determination in creating new social networks, finding employment, and supporting children and families. Camilla Cockerton has been a university lecturer in International Development and a volunteer with NGOs in Africa and New Zealand. Her passion for migration, gender, home and resilience started with her PhD research on Tswana women's migrancy in southern Africa. She now works as a Social Scientist for Building Research Association of New Zealand. This independent research company aims to improve the capacity in New Zealand to provide safer, healthier and more resilient buildings.
Acknowledgements -- Chapter 1 - Introduction -- Chapter 2 - Women "Runaways" -- Chapter 3 - Women's Migration Pre-1920 -- Chapter 4 - Single Women's Exodus from Botswana -- Chapter 5 - Single Tswana Women Migrants in South Africa -- Chapter 6 - Tswana Men Trying to Stop Women -- Chapter 7 - Policing the Boundaries - Intervention, Control and the Colonial State -- Chapter 8 - Men Trying to Stop Women's Migration -- Chapter 9 - Conclusion - Contestation of Gender in the "Land of the Desert".
Keywords: Emigration and immigration; Human geography; Identity politics; Africa -- History; Human Migration; Human Geography; Politics and Gender; African History